PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN SALON KECANTIKAN DI KECAMATAN PADANG BARAT KOTA PADANG - Famela, Zelli; Rostamailis, Rostamailis; Yanita, Merita (Journal of Home Economics and Tourism, 2016)
This research is based on the problem shows that the low employee motivation beauty salon in the District of West Padang that cannot to motivate them self both from the internal and external motivation in the work so that the performance obtained has not reached the standard a beauty salon. This research is aims to show the influence of work motivation on employee’s performance beauty salon Madya classification in work at salon. This research is descriptive-quantitative correlation. The population was the employee beauty salon madya classification of total 47 peoples, the sample of technique is total sampling so that amount same is 47 peoples. Data collection techniques using a questionnaire in the form of Likert scale.Based on analysis, the result of the data is obtained that the work motivation score percentage in the low category of total 61,31%, performance of employees beauty salon in low category of total 64,31%. Both of variables correlate solidly with total 0,743. Ha hypothesis explains that the influence a positive and significance between work motivation on performance beauty salon of employees to college are accepted on significance level of total 95%. The look for result of analysis level determination of given by contribution the work variable motivations is 55,2% to beauty salon employees performance, whereas there are is 44,8% other factor which can not known its contribution to employees performance.Key words: motivation, employees performance, beauty salon